HtrA4 is up-regulated during trophoblast syncytialization and BeWo cells fail to syncytialize without HtrA4 - Mary Mansilla; Yao Wang; Rebecca Lim; Kirsten Palmer; Guiying Nie (Scientific Reports, 2021)
Abstract The outer layer of the human placenta comprises syncytiotrophoblast, which forms through fusion of cytotrophoblasts (syncytialization), and plays a critical role in maternal–fetal communication including nutrient/oxygen transportation and hormone secretion. Impairment in syncytialization inevitably affects pregnancy outcomes. High temperature requirement factor A 4 (HtrA4) is a placental-specific protease, expressed by various trophoblasts including syncytiotrophoblast, and significantly elevated in preeclampsia at disease presentation. However, it is unknown whether HtrA4 is important for syncytialization. Here we first examined HtrA4 expression in primary human cytotrophoblasts during syncytialization which occurs spontaneously in culture, and in BeWo cells which syncytialize upon forskolin stimulation. The success of syncytialization in each model was confirmed by significant up-regulation/secretion of β-hCG, and the concurrent down-regulation of E-cadherin. In both models, HtrA4 mRNA and protein increased concomitantly with syncytialization. Furthermore, the secreted levels of β-hCG and HtrA4 correlated significantly and positively in both models. We next knocked out HtrA4 in BeWo by CRISPR/Cas9. Upon forskolin treatment, control BeWo profoundly up-regulated β-hCG and syncytin-1, down-regulated E-cadherin, and at the same time increased the formation of multinucleated cells, whereas BeWo cells without HtrA4 did not alter any of these parameters. Our data thus suggest that HtrA4 plays an essential role in syncytialization.